Women’s Work of Baptist Church in Guangdong and Guangxi（1835-1935） - LIU, Shibo (Journal of Research for Christianity in China (JRCC), 2025)
The Baptist Church was one of the earliest Protestant organizations to preach in China as Guangdong being the earliest missionary area. Later it entered Guangxi along the Xijiang River. Since the arrival of the first Baptist missionary in Macau in 1835, after a hundred years of development, the Guangdong-Guangxi Baptist Church, a church institution dominated by local Chinese Christians, has developed a large number of social services in the two provinces, including medical care, education, publishing, charity, children, youth and women’s work.This paper focuses on the women’s cause carried out by the Baptist Churches in Guangdong and Guangxi during 1835-1935, including the establishment and promotion of women’s status within the church, the role and contribution of women in various social undertakings established by the church. It also analyses the breakthrough impact and the positive promotion of Christianity on women’s liberation in China during the period of transition from traditional China to modern society at the late 19th and early 20th century.